1978
DOI: 10.1136/gut.19.6.514
|View full text |Cite
|
Sign up to set email alerts
|

Congenital hepatic fibrosis: the long-term prognosis.

Abstract: SUMMARY The long-term prognosis in congenital hepatic fibrosis has been assessed in 30 patients, 13 treated at Newcastle and 17 from other British centres. Twenty-four patients had been followed-up for more than five years from diagnosis. Shunt operations, performed in 18 patients, were successful in controlling haemorrhage with alow mortality (1/18), low incidence of recurrent haemorrhage (3/18) and portal-systemic encephalopathy (3/18) but with a higher incidence of postoperative jaundice (7/18). About a thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
2

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 17 publications
0
46
0
2
Order By: Relevance
“…All ARPKD patients manifest some degree of congenital hepatic fibrosis (CHF) caused by ductal plate malformation of the developing portobiliary system; some patients also have macroscopic dilations of the intrahepatic bile ducts, a combination termed Caroli's syndrome (7,13,14). Portal hypertension complicates CHF and often results in esophageal varices and hypersplenism (15)(16)(17)(18). Early-onset severe hypertension, often requiring multiagent therapy, occurs in most ARPKD patients (5).…”
mentioning
confidence: 99%
“…All ARPKD patients manifest some degree of congenital hepatic fibrosis (CHF) caused by ductal plate malformation of the developing portobiliary system; some patients also have macroscopic dilations of the intrahepatic bile ducts, a combination termed Caroli's syndrome (7,13,14). Portal hypertension complicates CHF and often results in esophageal varices and hypersplenism (15)(16)(17)(18). Early-onset severe hypertension, often requiring multiagent therapy, occurs in most ARPKD patients (5).…”
mentioning
confidence: 99%
“…With the progression of portal hypertension, the spleen increases and the platelet count decreases due to hypersplenism, developing portosystemic collateral circulation and creating oesophageal and gastric varices. The risk of bleeding increases with the increase in varice size [4,5,6]. Variceal bleeding can occur at any age, but is more common in older children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…In 1978, Kerr et al reported on the long-term prognosis of 30 patients with CHF from the United Kingdom, 24 of whom had been followed up for more than five years from diagnosis [22]. Shunt operations, performed on 18 patients, were successful in controlling hemorrhage and reducing recurrences with low incidence of PSE.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical portacaval shunt can also be considered. Portasystemic encephalopathy (PSE) and liver failure following a shunt procedure are usually less common in CHF than in those with cirrhosis [21,22].…”
Section: Discussionmentioning
confidence: 99%